PERAN ORGANISASI ISLAM DALAM PENGEMBANGAN EKONOMI ISLAM DI INDONESIA - Nurjannah, Siti Ifa; Angelia Hayya, Ratu Attak (SEKOLAH TINGGI ILMU SYARIAH ABU ZAIRI BONDOWOSO, 2025)
This research explores the role of Islamic organizations in promoting the development of Islamic economics in Indonesia. The study focuses on key activities such as education on sharia principles, the establishment of Islamic financial institutions, waqf management, policy advocacy, and the promotion of halal economic awareness. It investigates how prominent organizations like Nahdlatul Ulama, Muhammadiyah, the National Sharia Council (DSN), and the National Amil Zakat Agency (BAZNAS) contribute to building an inclusive Islamic economic ecosystem. Using a qualitative approach through literature review and interviews with organizational representatives, the findings indicate that Islamic organizations play a critical role in enhancing Islamic financial literacy, providing sharia-compliant financial services, and supporting national policy efforts. However, challenges remain, particularly in expanding access to these services and increasing public engagement. This study highlights the significant impact of Islamic organizations on the growth of sharia economics in Indonesia